Paeoniflorin alleviates high glucose-induced endothelial cell apoptosis in diabetes mellitus by inhibiting HRAS-activated RAS pathway - Wenting Yu; Hongchun Jiang (Endocrine Journal)
Paeoniflorin (Pae) can improve diabetes mellitus (DM), especially endothelial dysfunction induced by high glucose (HG). Molecularly, the mechanism pertinent to Pae and DM lacks further in-depth research. Hence, this study determined the molecular mechanism of Pae in treating DM through network pharmacology. The target of Pae was analyzed by TCMSP database, and DM-related genes were dissected by Genecards database and Omim database. PPI network was constructed for cross targets through Cytoscape 3.9.1 and STRING platform. GO and KEGG analyses were carried out on the cross targets. Protein molecular docking verification was completed by AutoDockTools and Pymol programs. Human umbilical vein endothelial cells (HUVECs) were separately treated with HG, Pae (5, 10, 20 μM) and/or HRAS overexpression plasmids (oe-HRAS). The cell viability, apoptosis and the protein expressions of HRAS and Ras-GTP were evaluated. There were 50 cross targets between Pae and DM, and VEGFA, EGFR, HRAS, SRC and HSP90AA1 were the key genes identified by PPI network analysis. GO and KEGG analyses revealed signal paths such as Rap1 and Ras. Molecular docking results confirmed that Pae had a good binding ability with key genes. In HG-treated HUVECs, Pae dose-dependently facilitated cell viability, attenuated cell apoptosis, and dwindled the expressions of HRAS and Ras-GTP, but these effects of Pae were reversed by oe-HRAS. In conclusion, Pae regulates the viability and apoptosis of HG-treated HUVECs by inhibiting the expression of HRAS.